Analisis Pengaruh Air Flow Ratio (AFR) dan Ukuran Partikel Limbah Tangkai Daun terhadap Produksi Syngas pada Downdraft Gasifier - Ilya Arina Rusyda; Fraulein Intan Suri; Niken Empina Putri (UNISTEK, 2026)
Abstract Tobacco leaf stalk’s waste can be used as alternative energy which known as biomass energy. Unfortunately this biomass energy was underused. It can be seen by the fact that tobacco waste only used for pesticide. This waste can be used to produce biomass energy by gasification method. Gasification is thermochemical method to produce syngas by converting solid fuel in gasifier by supplying gasification agent such as steam, air and other. This research used gasification method to convert tobacco leaf stalk’s waste to produced syngas (CO, H2, CH4) which can be an alternative energy. The purpose of this research is to review effect of air flow ratio (AFR) and effect of feed particle size to produce syngas by using downdraft gasifier. The process parameter are feed particle size 0,94-1,86 mm, 1,86-3,12 mm, 3,12-5,25 mm and AFR 1,5; 1,55; 1,6. The procedure of this research are drying, crushing, sizing, gasification process and analysis of gas compositions. The results show that the largest gas composition are produced at the size 1,86-3,12 mm with 1,6 AFR that produce syngas for H2 = 3.98% v; CO = 15.46% v; and CH4 = 1,32% v. Keywords : Gasifier, Gasification, Syngas, Tobacco leaf stalk’s waste